Managerialism: An Ideology and its Evolution - Christine Doran (International School for Social and Business Studies, 2016)
The article focuses attention on managerialism from the point of view of its ideological status. It traces the rise of managerialism, the main contributors to theorising about the nature of managerialism, and the characteristics and appeals of an outstanding managerialist text. The article begins by outlining the major features of the economic and social context in the United States, the United Kingdom and other Western countries that have contributed to the rise in the intellectual and social standing of the concept of managerialism. The problem of establishing consensus on the definition of managerialism is noted, as is the difficulty of positioning it within the conventional left-right political spectrum. The nature of an influential variant of managerialism known as 'socially responsible' management is then explored.